Nano-optical elements for the forming of 2D images - Goncharsky, A.A.; Durlevich, C.P. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
The paper is devoted to the mathematical modeling of synthesis of nano-optical elements. The possibilities of kinoform elements are studied in detail. It is shown that, in the problems of image formation, the kinoform elements have a number of advantages over the classical flat diffraction optical elements.